Positioning household waste transfer points: A municipality government-organized waste perspective - Eko Setiawan; Bekti Nugrahadi; Yesi Widiyastuti; Much Djunaidi; Suranto Suranto (Sustinere: Journal of Environment and Sustainability, 2018)
In response to growing importance of household waste management issue, this article deals with the positioning of household waste transfer points from a government-organized waste perspective. By taking Surakarta, a municipality in Central Java, Indonesia as an example, the problem in the municipality is formulated as an MILP, is approached with a capacity-weighted set covering method, and finally is solved by using software LINGO 11. The article concludes that the transfer point alternatives of Sondakan Kuburan, Norowangsan, SPSA, Pajang Rel, Bonoloyo and Kedung Tungkul should be selected in order to be able to serve all the household waste producers for the maximum household waste generated. On the contrary, the selection of Sondakan Kuburan, Bonoloyo and Kedung Tungkul only should be able to provide service to all of the household waste produced for the scenario of minimum amount of household waste.